2020
DOI: 10.1038/s41514-019-0039-5
|View full text |Cite
|
Sign up to set email alerts
|

Repository of proposed pathways and protein–protein interaction networks in age-related macular degeneration

Abstract: Age-related macular degeneration (AMD) is one of the commonest causes of sight loss in the elderly population and to date there is no intervention that slows or prevents early AMD disease progressing to blinding neovascularization or geographic atrophy. AMD is a complex disease and factors proposed to contribute to the development and progression of disease include aging, genetics, epigenetics, oxidative stress, pro-inflammatory state, and life-style factors such as smoking, alcohol, and high fat diet. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…An overlap of AMD risk genes with genes associated with other age-related disorders, such as coronary heart disease, diabetes, and Alzheimer's disease, has been noted previously. 5 Corroborating this, we find a high overlap (70%) of the 307 AMD risk genes with genes of other age-related diseases ( Fig. 1D and Supplementary Fig.…”
Section: Fig 1 a High-confidence Set Of Genes Associated With A Rissupporting
confidence: 62%
See 4 more Smart Citations
“…An overlap of AMD risk genes with genes associated with other age-related disorders, such as coronary heart disease, diabetes, and Alzheimer's disease, has been noted previously. 5 Corroborating this, we find a high overlap (70%) of the 307 AMD risk genes with genes of other age-related diseases ( Fig. 1D and Supplementary Fig.…”
Section: Fig 1 a High-confidence Set Of Genes Associated With A Rissupporting
confidence: 62%
“…1B), as noticed earlier. 5,15 Indeed, gene expression analyses of composite choroid/RPE and NR tissues obtained from human donor eyes 6 showed that AMD genes rarely belonged to ''expression group A'' (the top 1% of genes with highest transcript abundance), but were more often included in the upper 25% (''group B''), the middle 50% (''group C''), or the lower 25% (''group D'') expression classes ( Supplementary Fig. S3).…”
Section: Fig 1 a High-confidence Set Of Genes Associated With A Rismentioning
confidence: 99%
See 3 more Smart Citations